Fruit morphological diversity and quality of pulasan (Nephelium ramboutan-ake) from six populations in Riau, Indonesia - MARDALENI MARDALENI; HASAN BASRI JUMIN; NANDARIYAH NANDARIYAH; AHMAD YUNUS (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mardaleni, Jumin HB, Nandariyah, Yunus A. 2022. Fruit morphological diversity and quality of pulasan (Nephelium ramboutan-ake) from six populations in Riau, Indonesia. Biodiversitas 23: 2526-2533. Pulasan (Nephelium ramboutan-ake), which belongs to the Sapindaceae family, has economic value, but information on the morphological diversity and quality of its fruit is unknown. Thus, this study aimed to characterize the morphology and quality of pulasan fruits from six populations in Riau Province, Indonesia and observe the kinship among populations. A total of 18 qualitative and 13 quantitative characteristics were evaluated on 67 pulasan cultivars. The difference among morphological characteristics was to analysed using ANOVA and Duncan multiple range tests, while the kinship analysis used UPGMA. Results of the quantitative and qualitative characterization of pulasan fruits showed high diversity among populations. The fruit is oblong, and it has a uniform skin color, sweet taste, aril cream-white color, and aril that can be easily peeled from the seeds. These characteristics indicate good fruit quality. Dendrogram analysis divided the population into two large groups at 73% similarity. The first group consisted of the population of Kampar Kiri, Gunung Sahilan, and Kuok, whereas the second group consisted of the population of Bengkalis, Siak, and Kuansing. The results of this study provide baseline information to obtain potentially superior characteristics for breeding and conservation of genetic resources, which can be used as a basis for the conservation of the germplasm of pulasan.